If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49x + -112x + 64 = 0 Reorder the terms: 64 + 49x + -112x = 0 Combine like terms: 49x + -112x = -63x 64 + -63x = 0 Solving 64 + -63x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-64' to each side of the equation. 64 + -64 + -63x = 0 + -64 Combine like terms: 64 + -64 = 0 0 + -63x = 0 + -64 -63x = 0 + -64 Combine like terms: 0 + -64 = -64 -63x = -64 Divide each side by '-63'. x = 1.015873016 Simplifying x = 1.015873016
| -6+8n=-102 | | 81x-54x+9=0 | | -70-5y=-60 | | 2(5x+4)=35 | | 3(x-2)=2(4x+5) | | 16x+48x+36=0 | | 2x+2x-7=1 | | -8x+y-8=0 | | 2x^4-x^2-15=0 | | 3(4g-1)=18 | | x+22x+121=0 | | -2a-5=-33 | | 3(4-1)=18 | | x(x-9)=20 | | b-9+3b=12 | | x^4+2x^2+7=0 | | 5x+40=3(x+10) | | 11x-2x=306 | | x+24x+144=0 | | 9t+28=1 | | 3(2+5g)+4(3g-4)= | | 1.98g-12=0.87 | | 3.1=5.9-0.7x | | 36x-36x+9=0 | | x(3x-2)+2(3x-2)=0 | | 41.52=8g+3.76 | | 2x^2+x^2=100 | | 25x-70x+49=0 | | 8T^3-1=0 | | 2x^2+y^2=100 | | =-9x^2+24x+9 | | -7+n=-6 |